1996
DOI: 10.1128/iai.64.3.926-932.1996
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of the antimicrobial peptides human and rabbit defensins and porcine leukocyte protegrin against Mycobacterium tuberculosis

Abstract: Three independent assay methods were used to investigate the activities of antimicrobial peptides (human and rabbit defensins and protegrin from porcine leukocytes) against Mycobacterium tuberculosis in vitro. M. tuberculosis H37Ra was cultured in the presence of human neutrophil peptide 1, synthetic rabbit neutrophil peptide 1, or porcine protegrin 1 at 37؇C for 6 to 48 h, and antimycobacterial activity was measured by CFU assay. These peptides at a concentration of 50 g/ml showed significant antibacterial ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 40 publications
2
74
0
1
Order By: Relevance
“…Perhaps is at this time-point when CRAMP exerts its maximal antimicrobial activity, as suggested by the electronmicroscopy study that revealed strong CRAMP immunolabelling in the cell wall and cytoplasm of phagocytosed mycobacteria. Our in vitro study showed that CRAMP has modest anti-mycobacterial activity with similar minimum inhibitory concentration to that of LL-37, which is not better than that reported elsewhere for other anti-microbial peptides, such as human neutrophil peptides (HNPs) [21][22][23][24] and b-defensins [23,25]. The ultrastructural study showed cell membrane dissolution in the areas where CRAMP labelling was strong, indicating structural damage.…”
Section: Discussionsupporting
confidence: 54%
“…Perhaps is at this time-point when CRAMP exerts its maximal antimicrobial activity, as suggested by the electronmicroscopy study that revealed strong CRAMP immunolabelling in the cell wall and cytoplasm of phagocytosed mycobacteria. Our in vitro study showed that CRAMP has modest anti-mycobacterial activity with similar minimum inhibitory concentration to that of LL-37, which is not better than that reported elsewhere for other anti-microbial peptides, such as human neutrophil peptides (HNPs) [21][22][23][24] and b-defensins [23,25]. The ultrastructural study showed cell membrane dissolution in the areas where CRAMP labelling was strong, indicating structural damage.…”
Section: Discussionsupporting
confidence: 54%
“…91 The activity of NP-1 was followed by HNP-1, PG-1, Np-2, and HNP-2. 91 Similarly, Sharma and colleagues reported the half maximal inhibitory concentration (IC 50 ) and minimal inhibitory concentration (MIC) values for HNP-1 against the virulent M tuberculosis strain H37Rv as 0.8 μg/mL and 2.5 μg/mL, respectively. 90 They also demonstrated that HNP-1 inhibited 98% of H37Rv in 48 hours when used to treat infected murine J744A macrophages at a concentration of 40 μg/mL.…”
Section: Natural Peptides With Disulfide Bondsmentioning
confidence: 95%
“…[74][75][76][77][78][79][80][81][82]86,87 In the search for smaller molecules with possible anti-mycobacterial activity, studies have identified several antimicrobial peptides (AMPs), including fragments of antimicrobial proteins and their analogues. 7,[88][89][90][91][92][93][94][95][96][97][98][99][100][101] AMPs are typically short (less than 50 amino acid residues), mostly cationic and amphipathic. 99,102,103 They are promising as novel anti-mycobacterial agents, especially against strains of MDR M tuberculosis, due to their direct and swift bactericidal activity against a wide range of microbes and due to the low probability of resistance acquisition by pathogens.…”
Section: Drug Candidates Under Development For Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…Both human and rabbit defensins show activity against mycobacteria, including M. tuberculosis (Miyakawa et al 1996;Sharma et al 2000) and M. avium-intracellulare (Ogata et al 1992), even in the presence of divalent cations or physiologic salt concentrations. Although the plasma membrane of M. tuberculosis is the principal target for HNP-1 action, its DNA may be a secondary target (Sharma and Khuller 2001).…”
Section: Mycobacteria Spirochetes and Protozoamentioning
confidence: 99%